Correlation Between C-MYC, BCL-2, and BCL-6 Protein Expression and Gene Translocation as Biomarkers in Diagnosis and Prognosis of Diffuse Large B-cell Lymphoma - Zhang, YunXiang; Wang, Hui; Ren, Cuiai; Yu, Hai; Fang, Wenjia; Zhang, Na; Gao, Sumei; Hou, Qian (Frontiers in Pharmacology, 2019)
This study investigates the protein expression of C-MYC, BCL-2 and BCL-6 in diffuse large B-cell lymphoma (DLBCL) and their relationship with genetic abnormalities. A retro-spective study of 42 cases on paraffin-embedded tissue specimens diagnosed with DLBCL was performed using immunohistochemistry (IHC) and fluorescence in situ hy-bridization (FISH). The expression of C-MYC, BCL-2, BCL-6 protein and gene abnormali-ties in these tissue samples was analyzed. The relationship in genetic abnormalities and Ki-67, Hans classification, gender and age was also evaluated. It was found that the pos-itive rate of C-MYC expression was 47.6% (20/42), the rate of C-MYC gene abnormality was 26.2% (11/42), in which gene translocation accounted for 23.8% (10/42) and gene amplification 2.4% (1/42); C-MYC protein expression was positively correlated with C-MYC gene translocation (χ2=11.813; P=0.001); C-MYC gene translocation was mainly found in germinal center B cell type (χ2=4.029; P=0.045). The positive rate of BCL-2 pro-tein expression was 85.71% (36/42), the positive rate of translocation was 42.86% (18/42) and the amplification rate was 26.19% (11/42); the overexpression of BCL-2 protein was correlated with the BCL-2 translocation (χ2=3.407; P=0.029). The positive rate of BCL-6 protein expression was 45.24% (19/42), the positive rate of BCL-6 translocation was 14.29% (6/42) and the positive rate of BCL-6 amplification was 7.14% (3/42); the overex-pression of BCL-6 protein was significantly correlated with BCL-6 translocation (χ2=6.091; P=0.014). The Ki-67 index was significantly higher in C-MYC translocation cases than in non-C-MYC translocation cases (χ2=4.492; P=0.034). Taken together, our results suggest that the protein expression of C-MYC, BCL-2 and BCL-6 are positively correlated with their gene translocation. Overexpression of C-MYC, BCL-2, BCL- 6 pro-tein suggests the possibility of translocation. Therefore, immunohistochemical detection of C-MYC, BCL-2 and BCL-6 are useful in diagnosis and prognosis of DLBCL.